Myocardial Infarction Discharge Planning: Nurses, Approaches - Alsadeg Mohammed Kagygy, Saeeda; Ibrahim Yousif, Kaltoum; Abdel Hafeze Ali, Shamia; Sabri Ahmed, Faiza (Indian Journal of Nursing Sciences, 2024)
Background: Discharge planning is still become a problem for health services in hospital. Hospital discharge is a complex and challenging process for healthcare professionals, patients, and their family. Providing suitable health information is an important part of disease prevention and health promotion. Aim: This study aimed to assess nurses, approaches regarding discharge planning for patients with myocardial infarction (MI). Methods: This was a descriptive cross-sectional hospital-based. A total of 60 nurses were selected using convenient sampling method; data were collected using interview questionnaire and analyzed by a descriptive statistics using frequency and percentages through Statistical Package for the Social Sciences. Results: Ninety-six point seven of nurses educated patients about signs and symptoms and complication of MI, 90% of nurses gave nutritional counseling, 40% of nurses counsel MI patients about sports, 43.3% of nurses informed patients’ that, in case of dose missing, they should take the dose whenever they remember. Conclusion: Nurses had acceptable knowledge about discharge planning for patient with MI. Overall, nurses knowledge was 50.43% which considered acceptable.